Geopolymer concrete as a sustainable alternative to OPC - Adnan; Anas, Muhammad (Journal of Umm Al-Qura University for Engineering and Architecture, 2025)
Geopolymer concrete (GPC) serves as an environmental replacement for ordinary Portland cement (OPC) concrete to find sustainable construction materials quickly. Geopolymer concrete (GPC) shows market-ready potential through good mechanical properties and economic performance, yet it requires consistent access to particular raw ingredients like fly ash as well as heat treatment for peak outcomes, which determine its suitability for fields with limited resources. The field of GPC evaluation in Pakistan and comparable developing countries lacks studies about material analysis with locally available substances, while the financial assessment between GPC and OPC concrete exists in a limited form. Researchers at Sarhad University’s Concrete Engineering Laboratory in Peshawar, Pakistan, produced GPC using locally obtained Class F fly ash, GGBFS, and aggregates, and activators consisting of NaOH/Na₂SiO₃ with a concentration of 16 M. The materials underwent ASTM-compliant testing to verify their quality, and scientists prepared GPC and OPC samples to have similar compressive strength levels between 3,500 and 4,200 psi. The mixes maintained identical workability (75–100 mm slump) because of the presence of naphthalene-based superplasticizers. The results at day 3 showed GPC far exceeded OPC in compressive strength measurements by 2,420.5 psi compared to 1,404.7 psi, but reached the same strength level of ~ 4060 psi at day 28. The tensile strength of GPC exceeded that of OPC, with values of 4.3 MPa versus 3.9 MPa, and GPC demonstrated better flexural strength at 4.81 MPa relative to OPC at 4.3 MPa. The implementation of GPC reduced financial expenditure by 21.89 percent since it used fly ash along with reduced cement requirements to create the mixture, which lowered production costs from Rs. 7970 to Rs. 6225/m 3 . The widespread adoption of GPC encounters challenges due to its heat-curing method, which requires substantial energy consumption and possibly limited availability of top-quality fly ash throughout specific areas. The study demonstrates that GPC offers sustainable and financially advantageous infrastructure solutions when designed for specific regions, although the study identifies material supply chain and curing logistics as areas requiring improvement. GPC supports global efforts toward eco-friendly building by reducing waste emissions from industry.